Answer:
6
Step-by-step explanation:
Solve the absolutes: |-6| becomes 6
and |6| doesn't change and still is 6
Substitute: 6-6-(-6)
- * - = +
6-6+6 = 6
Answer:
zoomMeeting ID: 8570913589 Passcode: K58Ech
Explanation:
NO FACE SHOWING N^de ZOOM
Step-by-step explanation:
We need to find the 8 th term nth term is given as <span><span>an</span>=<span>a1</span>+(n−1)d</span>
n=8, d =-4 (common difference) <span><span>a8</span>=<span>a1</span>+(8−1)×d</span>
<span><span>a8</span>=1+7×(−4<span>)</span></span>
Answer:
3 1/4 + 2 1/3 = 67 / 12 = 57 1/2
Step-by-step explanation:
Conversion a mixed number to a improper fraction: 3 1/4 = 3 · 4 + 1
4
= 13
4
Conversion a mixed number to a improper fraction: 2 1/3 = 2 · 3 + 1
3
= 7
3
Add: 13
4
+ 7
3
= 13 · 3
4 · 3
+ 7 · 4
3 · 4
= 39
12
+ 28
12
= 39 + 28
12
= 67
12